Not in My Office: Rights in an Armed Campus Space - Heiskanen Benita (Cambridge University Press, 2022)
When the Texas legislature in August  allowed concealed handguns on campuses, the implementation of the legislation assumed a spatial meaning. At issue was not so much what the impact of firearms in educational establishments would be but where concealed guns could be carried and which specific locations were to be determined as exclusion zones. The decision-making process boiled down to a negotiation of rights by the federal government, state legislature, university, and members of the campus community. In particular, the question of gun rights was interpreted through notions of space, freedom, and privacy, as understood through amendments to the US Constitution.